A Journal Tempat Sampah Eco Dengan Konsep Internet of Things untuk Workspace Dalam Kondisi Lockdown - Faiz Alfein Kalbuadi; Mohammad Djalu Djatmiko (Aliansi Desainer Produk Industri Indonesia (ADPII), 2022)
Trash bins has always been a commodity of a paramount need, nonetheless, it is often taken for granted even though it is something that is connected directly to our basic human needs (especially food). Waste management system as an issue has never been completely resolved, and to make it worse, this new lifestyle in which we are living most of our lives in our homes instead of our usual workplaces. The pandemic forces us to stay at home and by nature makes us consume more consumables in our homes relative to the times in which we could eat or do our activities outside, hence producing more waste in our homes. Trash bins are used according to its name as a waste management system, but with the problems that we are in right now, trash bins need something new for them to be able to adapt in this era, increasing its efficacy. This project taps its feet into innovation waters by adopting the ever so hyped Go-Green movement as its pivotal core, while also challenging the new Industrial Revolution with IOT system in plans to achieve the new and fresh market in which Gen Y and Z are flourishing. Utilizing the Double Diamond Design Thinking Method in an effort to get user feedbacks in the process. This journal finds its conclusion in the form of a design, an Eco trash can with IOT functions in accordance of accommodating workspaces.